Customary laws and chieftaincy succession plans for nanun: a way forward for chieftaincy conflict management in Ghana - Cobb, Michael (2021)
Abstract: Chieftaincy is one of the African traditional institutions that coexist with modern forms of governance in post-independence Africa. Although the institution continues to enjoy support at local and national levels, succession disputes have generated numerous conflicts in recent times, as in the case of the Nanumba chieftaincy institution in northern Ghana. This research focuses on establishing how an institution supposedly beneficial for social peace has instead become a source of conflict. Also, the research explores the extent to which documented customary laws and chieftaincy succession plans, based on the shared beliefs of the people, could serve as an impetus for conflict management for Nanun and other chiefdoms in Ghana. Furthermore, it explores whether formalization of traditional institutions could help the cause of conflict prevention and management and thus bring about sustainable peace in areas experiencing chieftaincy-motivated conflicts in northern Ghana. The study used primary and secondary data. The primary data was collected through field observations and interviews conducted in 2019 and 2020 in the Nanumba North Municipality of Northern Ghana. The secondary data included Court rulings and archival materials retrieved from Regional and National House of Chiefs. It found that due to weak internal structures, the Nanumba chieftaincy is vulnerable to manipulation by elites and political leaders, rendering the institution dysfunctional and leading to an erosion of trust. The traditional regulatory mechanisms and customary practices and succession norms are applied selectively depending on the candidates involved and interpreted differently in an often incoherent and contradictory manner. Based on the findings, and on a comparison with the positive counter-examples of the Gonja and Asante chiefdoms, which have managed chieftaincy disputes more effectively, the study concludes that Nanumba customary norms and traditions regulating chieftaincy should be reexamined in a dialogue involving stakeholders and formalized to produce durable solutions that are accepted and upheld by the actors in different power positions and on different scales